Medical insurance benefits and health inequality: evidence from rural China - Wang, Xueyi; Qin, Cheng (Frontiers in Public Health, 2024)
Alleviating health inequality among different income groups has become a significant policy goal in China to promote common prosperity. Based on the data from the China Health and Retirement Longitudinal Study (CHARLS) covering the period from 2013 to 2018, this study empirically examines the impact of Integrated Medical Insurance System (URRBMI) on the health and health inequality of elderly rural residents. The following conclusions are drawn: First, URRBMI have elevated the level of medical security, reduced the frailty index of rural residents, and improved the health status of rural residents. Second, China exhibits "pro-rich" health inequality, and URRBMI exacerbates health inequality among rural residents with different incomes. This result remains robust when replacing the frailty index with different health modules. Third, the analysis of influencing mechanisms indicates that the URRBMI exacerbate inequality in the utilization of medical services among rural residents, resulting in a phenomenon of "subsidizing the rich by the poor" and intensifying health inequality. Fourth, in terms of heterogeneity, URRBMI have significantly widened health inequality among the elderly and in regions with a higher proportion of multiple-tiered medical insurance schemes.